WORK LIFE BALANCE AND WORK MOTIVATION MEDIATING THE INFLUENCE OF MUTATIONS ON THE PERFORMANCE OF BPJS KETENAGAKERJAAN SAMARINDA EMPLOYEES - Gusti Muhammad Indra Rosmana; Sri Mintarti, Dirga Lestari (Adisam Publisher, 2024)
This study aims to determine the effect of mutations on work life balance, work motivation, and employee performance at BPJS Ketenagakerjaan Samarinda. The research method used a questionnaire with a Likert scale and data analysis was carried out with Partial Least Square (PLS) and Structural Equation Model (SEM). The study population was all employees at the BPJS Ketenagakerjaan Samarinda Branch office, with a total population sample of 110 people. The results showed that job transfer has a significant effect on work-life balance and work motivation, but has no direct effect on employee performance. Work-life balance and work motivation have a significant influence on employee performance. The measurement and structural models showed high validity, good reliability, and decent predictive ability. This research confirms the importance of effective management in managing job transfer, work-life balance, and work motivation to improve employee performance. Suggestions include the development of work transfer policies that are oriented towards work-life balance, training programs to increase motivation, and further research to understand the full impact of work transfer.